2016
DOI: 10.1016/j.renene.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Development of a dynamic artificial neural network model of an absorption chiller and its experimental validation

Abstract: • A commercial absorption chiller has been tested in dynamic operating conditions on a semi-virtual test bench. • The absorption chiller was modelled in a dynamic way using artificial neural networks. • The model is validated using experimental data. • The neural model predictions are very satisfactory, absolute relative errors of the transferred energy are in 0.1-6.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The use of sorption chillers in the building sector is increasing because of their ability to use low‐grade heat for cold production. However, their operating conditions are highly dependent on the climate and building characteristics making their control difficult . Krzywanski et al built a neural network based model to predict the cooling capacity of a three‐bed adsorption chiller based on the operating conditions.…”
Section: Neural Network Applications Over a Building's Lifementioning
confidence: 99%
See 1 more Smart Citation
“…The use of sorption chillers in the building sector is increasing because of their ability to use low‐grade heat for cold production. However, their operating conditions are highly dependent on the climate and building characteristics making their control difficult . Krzywanski et al built a neural network based model to predict the cooling capacity of a three‐bed adsorption chiller based on the operating conditions.…”
Section: Neural Network Applications Over a Building's Lifementioning
confidence: 99%
“…However, their operating conditions are highly dependent on the climate and building characteristics making their control difficult. 31 Krzywanski et al 57 built a neural network based model to predict the cooling capacity of a three-bed adsorption chiller based on the operating conditions. Their method, easy to apply, constitutes a valuable alternative compare with other methods involving numerical analysis and/or experiments that are time consuming and expensive.…”
Section: Production and Distribution Systems Controlmentioning
confidence: 99%
“…The results showed that the required cooling load could be achieved with an error of less than 0.05%. Lazrak et al [19] implemented an ANN to predict outlet temperature and the transferred energy of the driving loop, heat rejection loop, and chilled water loop of a single-effect water-lithium bromide absorption chiller. The absolute relative errors of the transferred energy prediction were 0.1-6.6%.…”
Section: Introductionmentioning
confidence: 99%
“…This style of falling-film absorber is used in most absorption machines because it has several advantages, such as the high heat transfer coefficient, relatively low pressure drop, and sufficient absorption process compared to other tube arrangements. The absorption efficiency depends on many parameters, such as solution flow rate, tube geometry, and surface wetting, which governs flow around and between the tubes (Lazrak et al 2016;Li, Liu, and Liu 2016;Shirazi, Taylor, White, and Morrison 2016;Thangavelu, Myat, and Khambadkone 2017). Although the absorption chiller can use waste heat as an extra energy resource (Barrera et al 2012;Gomri 2010), the general adoption is still constrained by its relatively low coefficient of performance (COP).…”
Section: Introductionmentioning
confidence: 99%